The frequency of defective genomes in Omicron differs from that of the Alpha, Beta and Delta variants - Carolina Campos; Sergi Colomer-Castell; Damir Garcia-Cehic; Josep Gregori; Cristina Andrés; Maria Piñana; Alejandra González-Sánchez; Blanca Borràs; Oleguer Parés-Badell; Caroline Melanie Adombi; Marta Ibañez-Lligoña; Juliana Esperalba; et al. (Scientific Reports, 2022)
Abstract The SARS-CoV-2 Omicron variant emerged showing higher transmissibility and possibly higher resistance to current COVID-19 vaccines than other variants dominating the global pandemic. In March 2020 we performed a study in clinical samples, where we found that a portion of genomes in the SARS-CoV-2 viral population accumulated deletions immediately before the S1/S2 cleavage site (furin-like cleavage site, PRRAR/S) of the spike gene, generating a frameshift and appearance of a premature stop codon. The main aim of this study was to determine the frequency of defective deletions in prevalent variants from the first to sixth pandemic waves in our setting and discuss whether the differences observed might support epidemiological proposals. The complete SARS-CoV-2 spike gene was deeply studied by next-generation sequencing using the MiSeq platform. More than 90 million reads were obtained from respiratory swab specimens of 78 COVID-19 patients with mild infection caused by the predominant variants circulating in the Barcelona city area during the six pandemic waves: B.1.5, B.1.1, B.1.177, Alpha, Beta, Delta, and Omicron. The frequency of defective genomes found in variants dominating the first and second waves was similar to that seen in Omicron, but differed from the frequencies seen in the Alpha, Beta and Delta variants. The changing pattern of mutations seen in the various SARS-CoV-2 variants driving the pandemic waves over time can affect viral transmission and immune escape. Here we discuss the putative biological effects of defective deletions naturally occurring before the S1/S2 cleavage site during adaption of the virus to human infection.